High renewable energy (solar and wind) penetration hybrid energy systems in off-grid islands for deep decarbonization - Pascasio, Jethro Daniel A.
The Philippines has many off-grid islands relying on diesel generators for their electricity needs but with unreliable energy access, high greenhouse gas emissions and expensive electricity costs. With cheap wind electricity costs and high solar resource availability, there is an opportunity to use these renewable sources in decarbonizing and improving their energy access. This wok evaluated the techno-economic feasibility of putting up hybrid energy systems that incorporates solar and/or wind power in 143 existing off-grid island areas using HOMER Pro. The application optimized the hybrid system model for each area to obtain the architecture with the least electricity costs using the monthly load data from NPC-SPUG with typical hourly loads, and the solar and wind resource data sets from the Phil-LIDAR 2 Project. The results suggested the use of solar and wind power in 135 out of the 143 areas studied, solar power 5 areas, and wind power of 3 areas. The simulated hybrid energy systems require USD 1.102 billion (Php 55.19 billion) in capital costs and save USD 158.6 million (PHP 7.936 billion) annually. They showed higher sensitivities to wind energy potentials due to the cheap wing energy costs and high wind energy share of 62.32%. With the average renewable energy fraction of 84.46%, solar and wind power should be considered to improve energy access and reduce greenhouse gas emissions in off-grid island areas.